Potential role of gut microbiota in prostate cancer: immunity, metabolites, pathways of action? - Zha, Cheng; Peng, Zheng; Huang, Kunyuan; Tang, Kaifa; Wang, Qiang; Zhu, Lihua; Che, Bangwei; Li, Wei; Xu, Shenghan; Huang, Tao; Yu, Ying; Zhang, Wenjun (Frontiers in Oncology, 2023)
The gut microbiota helps to reveal the relationship between diseases, but the role of gut microbiota in prostate cancer (PCa) is still unclear. Recent studies have found that the composition and abundance of specific gut microbiota are significantly different between PCa and non-PCa, and the gut microbiota may have common and unique characteristics between different diseases. Intestinal microorganisms are affected by various factors and interact with the host in a variety of ways. In the complex interaction model, the regulation of intestinal microbial metabolites and the host immune system is particularly important, and they play a key role in maintaining the ecological balance of intestinal microorganisms and metabolites. However, specific changes in the composition of intestinal microflora may promote intestinal mucosal immune imbalance, leading to the formation of tumors. Therefore, this review analyzes the immune regulation of intestinal flora and the production of metabolites, as well as their effects and mechanisms on tumors, and briefly summarizes that specific intestinal flora can play an indirect role in PCa through their metabolites, genes, immunity, and pharmacology, and directly participate in the occurrence, development, and treatment of tumors through bacterial and toxin translocation. We also discussed markers of high risk PCa for intestinal microbiota screening and the possibility of probiotic ingestion and fecal microbiota transplantation, in order to provide better treatment options for clinic patients. Finally, after summarizing a number of studies, we found that changes in immunity, metabolites.